Development of Scalar Network Analyzer Based on Dual Channel Microwave Generator - Rajan, Suresh; Dahlan, Samsul Haimi (Evolution in Electrical and Electronic Engineering, 2024)
Microwave technologies are rapidly evolving, requiring sophisticated signal processing and control technology. This research develops a Scalar Network Analyzer (SNA) using a Dual Channel Microwave Generator (DCMC) to overcome standard SNAs’ frequency ranges, signal processing inefficiencies, and lack of dual channel capabilities. Low frequency (5 GHz) coupled line couplers will improve DCMC feedback systems. The project will provide a precise measuring system for transmission (S21) and reflection (S11). Microstrip-fabricated couplers can function at 5 GHz with a coupled loss < 10 dB. Simulation results for the coupler usingthe SynthNV microwave generator with dual channels indicated S11 at -18.965 dB, S21 at -2.473 dB, S31 at -9.561 dB, and S41 at -5.149 dB. The prototype integrated with DCMC has -0.099 dB at 2.8 GHz and -14,457 dB at 3.208 GHz. Adding a DCMC to the SNA framework improves microwave system accuracy, reliability, and efficiency, enabling future technology advances.